Auricular acupoint therapy in the adjuvant treatment of 2 cases of ventricular premature contraction (耳穴疗法治疗室性期前收缩2例) - LI Yuye (李玉叶); ZHANG Yuanyuan (张园园); ZHOU Xiaoyan (周晓艳); DOU Jinjie (窦金杰); CUI Liu (崔柳); ZHANG Yue (张悦); SHEN Juan (沈娟) (Journal of International Translational Medicine Limited, 2021)
To summarize the clinical treatment experience of 2 cases of ventricular premature contraction by auricular acupoint therapy. Based on the routine medication treatment, auricular acupoint therapy can effectively reduce the number of premature beats, improve palpitation, chest tightness and other symptoms, improve patient' compliance with treatment and nursing, and further improve the quality of life of patients. (本文总结2例室性期前收缩采用耳穴疗法治疗的经验。通过对室性期前收缩患者实施耳穴疗法后, 有效减少患者的早搏次数, 改善心慌、胸闷等症状, 提高患者对治疗和护理的依从性, 进一步提高患者生活质量。)